The Implementation Of Open Bidding In Filling Vacancy Chairs In The Local Government Of Sukabumi City - Depa Istia Putri (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
ABSTRACT Open Bidding is the process of filling high leadership positions openly within government agencies. The Personnel and Human Resources Development Department of Sukabumi City and the Selection Committee are the implementers of the Open Bidding policy responsible for implementing the Open Bidding policy. In 2021 Sukabumi City had the advantage of clinching the 1st place in the 2021 BKN Award for the Personnel’s National Coordination, meaning that the implementation of the Open Bidding policy in Sukabumi City is excellent. The research was aimed at finding out the implementation of Open Bidding in filling vacancies in office positions within the Government of Sukabumi City. The research method used was qualitative research method with descriptive approach. The techniques of collecting data applied in the research were observation, interview, and documentation. The techniques of validating data of the research deployed data triangulation techniques and technical triangulation techniques. The techniques of analyzing data were conducted through the process of reducing data, presenting data, and drawing conclusions. The data were analyzed qualitatively by applying an approach of the theory of implementation from Edward III. The results of the study indicate that the implementation of Open Bidding within the Regional Government of Sukabumi City has been running effectively observed from the communication built has been performing well, the human resources have been met, the disposition conducted has been going well, the bureaucratic structure has been implemented in accordance with the Operational Standards Procedure (SOP) in the set regulations that have been set. KEYWORDS: Implementation, Open Bidding, Best Practice